2021
DOI: 10.1186/s41983-021-00322-3
|View full text |Cite
|
Sign up to set email alerts
|

Neurological manifestations and neuroimaging findings in patients with SARS-CoV2—a systematic review

Abstract: Background The COVID-19 pandemic has drastically affected everyone in a hit or miss manner. Since it began, evidence of the neuro-invasive potential of the virus has been intensifying significantly. Several pathways have been hypothesized to elucidate the neurotropic nature of SARS-CoV2. It is the need of the hour to collect vital information. Objective To evaluate and correlate the neuro-radiological and neurological manifestations in patients dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…So far, only smaller cohort studies or single cases have reported cerebrovascular events, seizures, meningoencephalitis, and immune-mediated neurological diseases in patients, which are not suitable for quantitative analysis. Amongst these symptoms, COVID's effect on the neurological system is evident [ 20 ]. The patient also reported having dinner before her fainting episode, ruling out hypoglycemia as a potential cause.…”
Section: Discussionmentioning
confidence: 99%
“…So far, only smaller cohort studies or single cases have reported cerebrovascular events, seizures, meningoencephalitis, and immune-mediated neurological diseases in patients, which are not suitable for quantitative analysis. Amongst these symptoms, COVID's effect on the neurological system is evident [ 20 ]. The patient also reported having dinner before her fainting episode, ruling out hypoglycemia as a potential cause.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that the number of unreported stroke patients with COVID-19 infection is higher due to the availability and increased expense of imaging as well as possible "silent" clinical presentation. Finally, in a review, it was found that about 17.85% of patients who underwent neuroimaging had ischaemic changes suggestive for a stroke [68]. The inflammatory as well as the thrombogenic milieu seems to be a joint condition of cardiac and cerebrovascular injury in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a small sample of infected patients, a neuroradiological severity clinical index was correlated significantly with injury to the CNS (measures: Glial fibrillary acidic protein, total-tau, ubiquitin carboxyl-terminal hydrolase L1), and inflammation (C-reactive protein)[ 98 ]. A recent Cochrane review reported that stroke, paralysis, and altered mental status were the most frequent neurological disorders associated with COVID-19 infection[ 99 ]. The authors also suggested that COVID-19 could potentially induce new-onset of seizures, Guillain-Barre Syndrome, encephalitis, and other neurological disorders.…”
Section: Comparisons Of Mental Health Symptomatology Between Infected...mentioning
confidence: 99%